Stress and self-efficacy as long-term predictors for chronic low back pain: a prospective longitudinal study - Puschmann, Anne-Katrin; Drießlein, David; Beck, Heidrun; Arampatzis, Adamantios; Catalá, Maria Moreno; Schiltenwolf, Marcus; Mayer, Frank; Wippert, Pia-Maria (Journal of pain research, 2020)
Purpose: Psychosocial variables are known risk factors for the development and chronification of low back pain (LBP). Psychosocial stress is one of these risk factors. Therefore, this study aims to identify the most important types of stress predicting LBP. Self-efficacy was included as a potential protective factor related to both, stress and pain. Participants and Methods: This prospective observational study assessed n = 1071 subjects with low back pain over 2 years. Psychosocial stress was evaluated in a broad manner using instruments assessing perceived stress, stress experiences in work and social contexts, vital exhaustion and life-event stress. Further, self-efficacy and pain (characteristic pain intensity and disability) were assessed. Using least absolute shrinkage selection operator regression, important predictors of characteristic pain intensity and pain-related disability at 1-year and 2-years follow-up were analyzed. Results: The final sample for the statistic procedure consisted of 588 subjects (age: 39.2 (± 13.4) years; baseline pain intensity: 27.8 (± 18.4); disability: 14.3 (± 17.9)). In the 1-year follow-up, the stress types “tendency to worry”, “social isolation”, “work discontent” as well as vital exhaustion and negative life events were identified as risk factors for both pain intensity and pain-related disability. Within the 2-years follow-up, Lasso models identified the stress types “tendency to worry”, “social isolation”, “social conflicts”, and “perceived long-term stress” as potential risk factors for both pain intensity and disability. Furthermore, “self-efficacy” (“internality”, “self-concept”) and “social externality” play a role in reducing pain-related disability. Conclusion: Stress experiences in social and work-related contexts were identified as important risk factors for LBP 1 or 2 years in the future, even in subjects with low initial pain levels. Self-efficacy turned out to be a protective factor for pain development, especially in the long-term follow-up. Results suggest a differentiation of stress types in addressing psychosocial factors in research, prevention and therapy approaches.Keywords: low back pain, psychosocial risk factors, stress, self-efficacy, MiSpEx
Gesehen am 30.04.2020